GEJOLAK INDO-PASIFIK: ANALISIS KEBIJAKAN AUSTRALIA DALAM MERESPON ANCAMAN TIONGKOK DI KAWASAN INDO-PASIFIK - Arfa Bahrul Ulum; Reni Windiani (Journal of International Relations Diponegoro, 2023)
Australia conducts defense cooperation with Japan within the framework of the Reciprocal Access Agreement (RAA). The signing of this cooperation was carried out online on January 6, 2022. The signing of this defense cooperation is the second in a period of 6 months after previously Australia did it with the United States and Britain. Meanwhile in the Indo-Pacific, China continues to exert influence in the region and carries out several threatening activities. This research will try to explain the phenomenon between Australia and Japan and its relationship with China. This research will use the formulation of the problem "Why does Australia carry out defense cooperation with Japan through a Reciprocal Access Agreement?". The research method used in this study is a qualitative research method and uses the balance of threat theory. The findings in this study are that Australia is conducting defense cooperation with Japan through the RAA because there are threats made by China against Australia so that Australia is carrying out this cooperation as a form of response to increase strength over the threats that are present. As for suggestions for further research to develop it by discussing further about the implementation of this RAA cooperation.